Strength of Excitation Is Negatively Associated with Aggressive Behavior after Interpersonal Rejection - Rajchert, Joanna; Winiewski, Mikołaj (Frontiers in Psychology, 2017)
This study explored how the Pavlovian temperamental traits strength of excitation (SE) and strength of inhibition (SI) were related to rejection and aggression. We predicted that rejection would increase aggression, but that higher SE and SI would mitigate this effect. Participants (n = 117) completed Strelau and Zawadzki’s (1998) Pavlovian Temperament Survey. A week later they were told that a peer wanted (acceptance) or did not want (rejection) to work with them and they were given a chance to react aggressively by damaging that person’s chance of getting a job. We found that only high SE was negatively related to rejected individuals’ aggression. The results are related to the diathesis-stress and catalyst models’ accounts of the role of temperament in shaping experience of social stress.